RESPONSE OF PHYSIOLOGICAL AND HISTOLOGICAL TRAITS TO ENZYME SUPPLEMENTATION AND SOAKING OF DIETS CONTAINING CORN AND WHEAT OF THE LAYNING HENS - & et al., Al Rubaee (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted at Poultry Research Station Animal Resources Research Department–State Board of Agricultural Research/ Ministry of Agriculture in Abu Ghraib, which included two experiment to study the effect of enzyme  supplementing and soaking to the diets of the laying hens containing corn and wheat on productive performance.Three hundred Brown-egg hens (ISA Brown) 40 weeks of age were used in this experiment after preliminary period for two weeks. Layer hens distributed randomly to ten treatments with 2 replicates (15 hens per replicate); and fed on diets according to the age periods in ISA guide. Treatments were as follows: T1: Control group (100% corn).T2: 100% corn with soaking. T3: 100% corn with enzymes. T4:100% corn with soaking and enzymes. T5: 33% corn replacement wheat with soaking. T6: 33% corn replacement   wheat and with enzymes. T7: 33% corn replacement wheat with soaking and enzymes. T8: 66% corn replacement wheat with soaking. T9: 66% corn replacement wheat with enzymes. T10: 66% corn replacement wheat with soaking and enzymes. The results showed a significant increase  (P